Formation of reactive oxygen and nitrogen species by repetitive negatively pulsed helium atmospheric pressure plasma jets propagating into humid air. (8th June 2015) - Norberg, Seth A; Johnsen, Eric; Kushner, Mark J
Abstract: Atmospheric pressure plasma jets have many beneficial effects in their use in surface treatment and, in particular, plasma medicine. One of these benefits is the controlled production of reactive oxygen and nitrogen species (RONS) in the active discharge through the molecular gases added to the primary noble gas in the input mixture, and through the interaction of reactive species in the plasma effluent with the ambient air. In this computational investigation, a parametric study was performed on the production of RONS in a multiply pulsed atmospheric pressure plasma jet sustained in a He/O2 mixture and flowing into ambient humid air. The consequences of flow rate, O2 fraction, voltage, and repetition rate on reactant densities after a single discharge pulse, after 30 pulses, and after the same total elapsed time were investigated. At the end of the first discharge pulse, voltage has the greatest influence on RONS production. However, the systematic trends for production of RONS depend on repetition rate and flow rate in large part due to the residence time of RONS in the plasma zone. Short residence times result in reactive species produced by the previous pulse still being in the discharge tube or in the path of the ionization wave at the next pulse. The RONS therefore accumulate in the tube and in the near effluent on a pulse-to-pulse basis. This accumulation enables species requiring multiple reactions among the primary RONS species to be produced in greater numbers.